Pengaruh Zakat Terhadap Tingkat Kemiskinan Masyarakat Kabupaten Padang Lawas Utara Dengan Metode Regresi Linear - Irsal Ahmadi Siregar, Irsal; Sugianto, Sugianto; Siregar, Irsal Ahmadi (Bursa : Jurnal Ekonomi dan Bisnis, 2024)
This research aims to (1) find out how zakat collection affects the poverty level of the North Padang Lawas population. (2) Examining the impact of zakat distribution on the level of poverty of North Padang Lawas residents. (3) Examining the impact of distribution and collection of zakat on the degree of poverty of North Padang Lawas residents. The income level and economic growth rate of people with simple and developed lives have the same characteristics, apart from that, the increase in income per capital in developing countries is still very low. The income gap between high-income and low-income groups is still clearly visible in North Padang Lawas district. In this case, the collection of zakat funds for North Padang Lawas district uses the linear regression method. From 2019 to 2021, it was concluded that the amount of productive zakat distributed in North Padang Lawas district must be increased, because productive zakat is one of the factors that can alleviate poverty.